Simulated chorus attracts conspecific and heterospecific Amazonian explosive breeding frogs. (1st October 2020) - Fouquet, Antoine; Tilly, Thomas; Pašukonis, Andrius; Courtois, Elodie A.; Gaucher, Philippe; Sebastian Ulloa, Juan; Sueur, Jérôme
Abstract: In tropical regions, some anuran species breed "explosively", reproducing in massive and highly diverse aggregations during a brief window of time. These aggregations can serve as acoustic beacons, attracting other anurans toward seasonal ponds. We hypothesize that conspecific and heterospecific calls play a role in navigation toward ponds and synchronization of reproduction among species. We simulated a chorus of two species ( Trachycephalus coriaceus and Chiasmocleis shudikarensis ) with contrasting call characteristics (low‐frequency vs. high‐frequency) and reproductive strategies (strict pond breeder vs. opportunistic) near known explosive breeding sites. We predicted that choruses of T. coriaceus are more attractive to heterospecifics than of C. shudikarensis because the first provides a more reliable indicator of a suitable breeding pond and a better long‐distance signal. We found that both choruses attracted conspecific frogs to the playback outside a natural breeding event. As predicted, heterospecifics were attracted only by low‐frequency calls of T. coriaceus that breeds exclusively in large ponds, but not by higher frequency calls of C. shudikarensis that also breeds in small pools not suitable for other species. Our study presents the first experimental evidence that tropical explosive breeding anurans are attracted to conspecific and heterospecific choruses. The contrasting effect of the playback of the two species on heterospecifics suggests that the attractive effect of a chorus depends on the reproductive strategy of both the sender and the receiver. Given the abundance and diversity of communities in tropical ecosystems, the use of heterospecific acoustic cues may prove widespread and requires further investigation. Abstract in Portuguese is available with online material. Abstract : Up to a dozen different species of frogs can breed simultaneously in temporary ponds in Amazonia during so‐called explosive‐breeding events, because they are very brief (about 24h) and very loud (about 100 dB). We simulated a chorus of two species with contrasting call characteristics and reproductive strategies near known explosive breeding sites to test if heterospecific and conspecific signals attract frogs. Both signals attracted conspecifics but only the low frequency signal of Trachycephalus, a large tree‐frog that only breeds in ephemeral ponds, attracted other frogs. RESUMO: Nas regiões tropicais, algumas espécies de anuros possuem "reproduções explosivas", nas quais agregações massivas e altamente diversas se formam durante um curto período de tempo. Tais agregações podem funcionar como indicadores acústicos, atraindo outras espécies de anuros para as poças sazonais. Nós hipotetizamos que cantos coespecíficos e heteroespecíficos desempenham papéis na navegação em direção às poças e na sincronicidade de reprodução entre as espécies. Nós simulamos o coro de duas espécies ( Trachycephalus coriaceus e Chiasmocleis shudikarensis ) próximo de reconhecidos sítios de reprodução explosiva. Baseado no fato que essas espécies possuem características contrastantes de canto (baixa vs. alta frequência) e de estratégias reprodutivas (reprodução restrita a poças vs. não restrita), nossa predição foi que o coro de T. coriaceus seria mais atrativo para indivíduos heteroespecíficos, já que representa um indicador mais confiável de um ambiente adequado para a reprodução e possui um melhor alcance do sinal em longas distâncias. Nós descobrimos que ambos os coros atraíram indivíduos coespecíficos à reprodução da gravação simulando um evento reprodutivo natural. Como previsto, indivíduos heteroespecíficos foram atraídos unicamente pelos cantos de baixa frequência de T. coriaceus, que reproduz unicamente em grandes poças, mas não pelos cantos de alta frequência de C. shudikarensis, que também reproduz em poças menores e não adequadas a outras espécies. Nosso estudo representa a primeira evidência experimental que anuros tropicais de reprodução explosiva são atraídos por cantos coespecíficos e heteroespecíficos. O efeito contrastante da reprodução da gravação destas duas espécies em indivíduos heteroespecíficos sugere que a influência atrativa dos coros dependem das estratégias reprodutivas tanto dos emissores quanto dos receptores. Considerando a abundância e diversidade das comunidades em ecossistemas tropicais, o efeito de indicadores acústicos heteroespecíficos pode ser mais comum, e requer novas investigações.